Bibliometric analysis of publications from the last 16 years on the use of Virtual Reality as a teaching tool in the health area (Research, Society and Development, 2021)
Virtual Reality is one of the most innovative technologies today and can be applied in education in several areas of knowledge, including the training of health professionals. In health education, this application is the focus of several types of research, so the need for a bibliometric study to identify the points of interest in this topic. This study presents the results of a bibliometric analysis on the use of virtual reality in health education and to report the characteristics of these studies. The articles were searched on the Web of Science, and those published between 2004 and 2020 on the topic were included. Histcite© and VOSviewer software were used for data analysis. In total, 1705 articles were identified. The analysis of the characteristics of the publications and the co-citation and co-occurrence networks of words showed that the main use of this technology in health education has been the training of surgical students, and positive results in increasing student performance have been identified in several studies. It was also possible to identify that in 2020, there was a significant increase in the number of publications on this topic, possibly due to the pandemic of the SARS-CoV-2 virus and the consequent need to implement new methodological approaches in health education. Thus, virtual reality can be considered an important tool in the education and training of new health professionals, assisting in the acquisition of knowledge and skills in several areas of this field, mainly in the surgical area.